Development of small and medium enterprises to export to external barriers - Ranjbar, Saeed; Abbasi, Ebrahim (Pure and Applied Science Advances, 2014)
The aim of this study is to explore the current exportchallenges for SMEs in Pakistan and how these barriers affect the SMEs. Oneindustry (textile) was selected for this study. Findings of this study showedthat internal barriers are more influential than external barriers. This studyis limited to one industry . This study disseminates the attention of SMEsexport managers towards the genuine and main problems coming across the SMEexports so they can deal with these barriers to magnify their exports asinternal barriers are more controllable as compared to external barriers. Thisstudy offers insights into SME export barriers in iran.